Longitudinal shock of two elastic bars with one spherical end - Nguyen Thuc An; Nguyen Dang To; Nguyen Hung Son (Vietnam Journal of Mechanics)
In this paper, authors researched a problem about longitudinal shock of two free elastic bars with one spherical end in interval 0 < t < 2l2/ a2 . Authors defined wave function in the bars, tress, strain and velocity of every section.